Influence of pterygium size on corneal higher-order aberration evaluated using anterior-segment optical coherence tomography - Minami, Keiichiro (BMC Ophthalmol, 2018)
BACKGROUND: The prospective observation study aimed to evaluate changes in corneal higher-order aberrations induced by advancement of pterygium using an anterior-segment optical coherence tomography (AS-OCT) and Zernike aberration analysis. METHODS: The corneal topography of 284 eyes with primary pterygia originating from the nasal region was measured using an AS-OCT (SS-1000, Tomey). With anterior corneal elevation data, Zernike polynomial coefficients were calculated in diameters of 1.0, 3.0, and 5.0 mm, and the coma, spherical, coma-like, spherical-like, and total higher-order aberrations were obtained. Pterygium size was also measured as a ratio of positions of the pterygium end with respect to the corneal diameter and categorized in eight classes: less than 15%, 15–20%, 20–25%, 25–30%, 30–35%, 35–40%, 40–45, and 45% or larger. Increases in the aberrations were analyzed with reference to those in eyes with pterygium size < 15%. RESULTS: The mean age of the participants was 69.3 years, and the pterygium size ranged from 2 to 57% (mean: 28.8%). The coma aberration significantly increased when the pterygium size was 45% or larger in 1.0 and 3.0 mm diameters and over 25–30% in 5.0 mm diameter. Similar increases were found in the pterygium sizes exceeding 45, 40, and 25%, respectively, in the coma-like, spherical-like, and total higher-order aberrations. On contrast, there was no increase in the spherical aberration. CONCLUSION: Increases in higher-order aberrations reflected the pterygium size, and significant aberrations were induced in 5.0 mm diameter when the end exceeded 25% of corneal diameter. The use of AS-OCT and Zernike analysis could enable objective grading of pterygium advancement based on changes in corneal optics. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12886-018-0837-8) contains supplementary material, which is available to authorized users.